Factors behind exiting from the Bangladesh pharmaceutical industry and closing down the pharma businesses unit of GlaxoSmithKline Bangladesh Ltd. - Islam, Md. Saiful (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.